1988
DOI: 10.1002/jcb.240360207
|View full text |Cite
|
Sign up to set email alerts
|

Heparanases and tumor metastasis

Abstract: The successful penetration of endothelial basement membranes is an important process in the formation of hematogenous tumor metastases. Heparan sulfate (HS) proteoglycan is a major constituent of endothelial basement membranes, and we have found that HS-degradative activities of metastatic B16 melanoma sublines correlate with their lung-colonizing potentials. The melanoma HS-degrading enzyme is a unique endo-beta-D-glucuronidase (heparanase) that cleaves HS at specific intrachain sites and is detectable in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
263
2
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(280 citation statements)
references
References 53 publications
10
263
2
5
Order By: Relevance
“…MMP-2 and -9 are suggested to play a major role in metastasis (Kugler, 1999;Westermarck and Kahari, 1999). Heparanase activity has also been found to correlate with the metastatic potential of various types of cancer cells (Nakajima et al, 1988). In this study the dose-dependent inhibition of NAC-HCPS on the invasion of tumour cells into Matrigel has been observed ( Figure 6).…”
Section: Discussionsupporting
confidence: 54%
“…MMP-2 and -9 are suggested to play a major role in metastasis (Kugler, 1999;Westermarck and Kahari, 1999). Heparanase activity has also been found to correlate with the metastatic potential of various types of cancer cells (Nakajima et al, 1988). In this study the dose-dependent inhibition of NAC-HCPS on the invasion of tumour cells into Matrigel has been observed ( Figure 6).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies showed that heparanase is capable of degrading the heparan sulfate chains of HSPGs widely ranged in BM and ECM and enhancing the invasion and metastasis of malignant cells (4,5,8,19,20). In this study, we have observed heparanase message expression even in very early invasive carcinomas within the lamina propria of gastric mucosa, but not in the normal epithelium or noninvasive carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HSPG catabolism is observed in inflammation, wound repair, diabetes, and cancer metastasis, suggesting that enzymes that degrade the HS chains play important roles in pathologic processes (3, 4). Furthermore, malignant cells are capable of modulating cellular interactions with HSPGs by producing and releasing a HS-degrading enzyme, heparanase (3,7,27,28). Recently, we reported that purified, high M r subpopulations of cell surface HS were more sensitive to heparanase action than secreted HS (29).…”
mentioning
confidence: 99%